Liquidity risk : managing funding and asset risk - Banks, Erik; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
Liquidity Management is now a core consideration for banks and other financial institutions following the collapse of numerous well-known banks in 2007-8. This timely new edition will provide practical guidance on liquidity risk and its management - now mandatory under new regulation.
Keywords: Business; Business enterprises -- Finance; Corporations -- Finance; Banks and banking; Investment banking; Securities; Risk management